2020
DOI: 10.4187/respcare.07600
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk Factors in Preterm Infants Treated with High-Frequency Jet Ventilation

Abstract: BACKGROUND: High-frequency jet ventilation (HFJV) has been used in conjunction with conventional ventilation for premature infants with respiratory failure. We sought to identify parameters that were associated with mortality in subjects who underwent HFJV. METHODS: Subjects were enrolled if birthweight was^2,000 g and they were^34 weeks gestational age. Subjects were excluded if they received HFJV at the time of admission because we aimed to study subjects who failed conventional ventilation. Subject demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…When initiating HFJV in premature neonates, initial PIP is usually started slightly above (ie, 2-5 cm H 2 O above) the PIP on the conventional ventilator and adjusted for "appropriate" chest wiggle. 12 For patients in the pediatric ICU, the initial PIP may be set in a similar manner, although larger patients may require a high ( 40 cm H 2 O) initial PIP. 8,9 Attenuation of the PIP through the large airways and bronchi results in lower pressure in the terminal airways and alveoli.…”
Section: Settings and Technical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…When initiating HFJV in premature neonates, initial PIP is usually started slightly above (ie, 2-5 cm H 2 O above) the PIP on the conventional ventilator and adjusted for "appropriate" chest wiggle. 12 For patients in the pediatric ICU, the initial PIP may be set in a similar manner, although larger patients may require a high ( 40 cm H 2 O) initial PIP. 8,9 Attenuation of the PIP through the large airways and bronchi results in lower pressure in the terminal airways and alveoli.…”
Section: Settings and Technical Considerationsmentioning
confidence: 99%
“…8,9 Despite the lack of high-quality evidence, the use of HFJV may be increasing as there have been a number of single-center experiences published since 2015. [8][9][10][11][12] The purpose of this review is to discuss the physiologic principles behind HFJV, examine the evidence supporting its use in neonatal and pediatric ICUs, give meaningful guidance for clinical application, and highlight potential areas for future research.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, survival is an important outcome, but in the future we should consider including a composite outcome, such as survival without significant morbidity, in premature neonates because many survivors carry significant morbidities such as cerebral palsy, bronchopulmonary dysplasia, developmental delay, increased hospitalizations, and other long-term health sequelae. 12 The renewed interest in HFJV in the neonatal ICU has illustrated the need for randomized controlled trials investigating HFJV as both a rescue mode like in the study by Wheeler et al 8 and as an elective strategy to prevent bronchopulmonary dysplasia. Given the relative rarity of HFJV use and logistical challenges associated with a randomized controlled trial, it is likely that observational data will be our best source of evidence for now.…”
Section: See the Original Study On Page 1631mentioning
confidence: 99%
“…7 Despite the lack of high-quality, high-level supporting data, HFJV is widely used in neonatal ICUs as a rescue mode and as an elective mode intended to reduce bronchopulmonary dysplasia and chronic lung disease. In this issue of RESPIRATORY CARE, Wheeler et al 8 reported on risk factors for mortality in 53 premature neonates treated with rescue HFJV in their quaternary neonatal ICU. The overall survival rate was 74%, and univariate analysis revealed gender, gestational age, postmentrual age at HFJV initiation, born < 28 weeks gestational age, weight, length of stay, arterial access, inhaled nitric oxide, patent ductus arteriosus, F IO 2 , peak inspiratory pressure at 1 h after HFJV initiation, and oxygen saturation index at 4 h after HFJV were all statistically different between survivors and non-survivors.…”
mentioning
confidence: 99%
“…As the OSI could be monitored continuously and transcutaneously, in contrast to the commonly used OI that requires blood sampling, the OSI might be used for real-time and bedside guidance during the crucial first hours of life. We have recently demonstrated that both the OI and OSI predict adverse outcomes in infants with CDH, but up until now, studies have focused on either the predictive value of OSI measurements at pre-specified time points or the comparability of paired OI and OSI measurements [9][10][11][12][13][14][15]. Hence, studies on the predictive value of continuous OSI measurements are scarce, especially in infants with CDH [16].…”
Section: Introductionmentioning
confidence: 99%